INTERAKSI FAKTOR POLIMORPHISME GEN ENDHOTELIAL NITRIC OXIDE SINTASE (eNOS) DENGAN FAKTOR – FAKTOR RESIKO TERHADAP PREGNANT INDUCED HYPERTENSION (PIH) - Mochammad Erwin Rachman (Fakultas Farmasi UMI, 2012)
The aim of the study was to discover the effect of interaction polymorphism endhotelial nitric oxide synthase (eNOS) polymorphism gene with mother’s age, parity, and body mass index (BMI) on the incidence of Pregnant Induced Hypertension (PIH) using a nested case control study. The number of subjects was 29 pregnant mothers whose pregnancy was ≥ 20 weeks. The examination of endotelial nitric oxide synthase (eNOS) polymorphism gene was done by polymerase chain reaction (PCR) modified by Rigat. The result of the study indicate that the nitric oxide synthase (eNOS) polymorphism gene of genotype GG the risk more than the genotype non GG. Genotype GG 1,8 means that the risk for hypertension is high, and the age less than 20 years and over 35 years has 3,78 times risk for PIH, while at the multípara , the risk is 2,16 times compared to the primípara. So that at the high BMI , the risk is 1,67 times compared to the normal BMI. Interaction of the genotype GG and ages < 20 years and >35 years have risk for PIH will have a greater risk for PIH than another of the interaction genotype non GG, parity, and BMI. Interaction between gene factor with environment will enlarge risk suffer PIH.Keyword : Pregnant induced hypertension, mother’s age, parity, BMI, eNOS gen polymorphism.